The effect of overlapping on the primary stability of osteochondral grafts in mosaicplasty - (:unkn) unknown (SPRINGER, 2008)
Our goal was to determine the primary stability of overlapping osteochondral grafts used in mosaicplasty by studying the effect of overlapping in an ex vivo model. Osteochondral grafts, 10 mm in diameter, were transplanted from the trochlea of cow femurs to the weight-bearing area of the lateral femoral condyle with 0, 15, or 30% overlap. The grafts were pushed in with a probe at a rate of 2 mm/min, and load (N)-displacement (mm) curves were recorded. In Group I (control, 0% overlap), insertion 1 and 2 mm below the cartilage level could be reached at 572.3 +/- 273.6 and 999.3 +/- 427.6 N, respectively. In Group II (15% overlap), insertion 1 and 2 mm below the cartilage level could be reached at 263.6 +/- 91.7 and 746.6 +/- 88.0 N, respectively. In Group III (30% overlap), insertion 1 and 2 mm below the cartilage level could be reached at 179.4 +/- 31.2 and 657.0 +/- 106.5 N, respectively. The loads that were necessary to produce a 1-mm dent in the grafts were significantly different between Groups I and II and Groups I and III (p < 0.05). These results suggest that stability may be reduced by graft overlapping in mosaicplasty surgery. The results of this ex vivo animal study contribute to a more complete understanding of the primary stability of osteochondral grafts in an overlapping position as well as postoperative protocols.
Keywords: mosaicplasty; biomechanics; graft; overlapping; primary stability